2013
DOI: 10.1002/syn.21680
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of D2 receptor specific binding in obese and normal‐weight individuals using PET with (N‐[11C]methyl)benperidol

Abstract: Previous PET imaging studies have demonstrated mixed findings regarding dopamine D2/D3 receptor availability in obese relative to non-obese humans. Nonspecific D2/D3 radioligands do not allow for separate estimation of D2 receptor (D2R) and D3 receptor (D3R) subtypes of the D2 receptor family, which may play different roles in behavior and are distributed differently throughout the brain. These radioligands are also displaceable by endogenous dopamine, confounding interpretation of differences in receptor avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
113
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(129 citation statements)
references
References 48 publications
(122 reference statements)
7
113
3
Order By: Relevance
“…For instance, work with [ 11 C]raclopride has demonstrated reductions in striatal D 2/3 R availability in both severely obese ) and OB (Haltia et al, 2007) individuals when compared with NW controls. Complicating the picture further, [ 11 C]raclopride findings are not consistent with studies that utilized [ 11 C]FLB457, which demonstrated BMI was positively associated with amygdalar D 2/3 R availability (Yasuno et al, 2001) or [ 11 C] NMB, where no association between BMI and striatal D 2/3 R availability was found (Eisenstein et al, 2013). Such lack of agreement across the obesity and PET dopamine literature is complex and several factors could be responsible including differences in tracers and research participants.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…For instance, work with [ 11 C]raclopride has demonstrated reductions in striatal D 2/3 R availability in both severely obese ) and OB (Haltia et al, 2007) individuals when compared with NW controls. Complicating the picture further, [ 11 C]raclopride findings are not consistent with studies that utilized [ 11 C]FLB457, which demonstrated BMI was positively associated with amygdalar D 2/3 R availability (Yasuno et al, 2001) or [ 11 C] NMB, where no association between BMI and striatal D 2/3 R availability was found (Eisenstein et al, 2013). Such lack of agreement across the obesity and PET dopamine literature is complex and several factors could be responsible including differences in tracers and research participants.…”
Section: Discussionmentioning
confidence: 72%
“…This relationship did not extend to non-OB individuals, where no associations between striatal D 2/3 R availability and BMI have been found with [ 11 C]raclopride (Caravaggio et al, 2013). Work done with the D 2 -high affinity tracer, [ 11 C]N-methyl-benperidol (NMB), failed to show any striatal D 2/3 R availability alterations between NW and severely obese individuals (Eisenstein et al, 2013 . Other regions investigated with [ 18 F]fallypride have shown slightly higher D 2/3 R availability (not statistically significant) in the SN/VTA of OB as compared with NW females (Savage et al, 2014) and a positive linear association between D 2/3 R availability and BMI in the caudate and putamen of a large cohort of individuals with a wide BMI range (range 18-45 kg/m 2 ) (Guo et al, 2014).…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, DA is also released post-prandially, possibly mediating the successive devaluation of food reward during a meal (de Auraujo et al Neuron 2008) in addition to its release during anticipation and acute consumption of food rewards. Excessive eating, similar to chronic drug consumption, progressively leads to alterations in the dopaminergic system, specifically to a down-regulation of striatal dopamine 2 and/or 3 (D2/D3) receptors (De Weijer et al, 2011;Eisenstein et al, 2013;Geiger et al, 2009;Nader et al, 2006;Thanos, Michaelides, Benveniste, Wang, & Volkow, 2007;Wang et al, 2001). This down-regulation, among other factors, is assumed to induce a shift to cue-triggered habit-like consumption (Volkow et al, 2013).…”
Section: Neurobiological Basismentioning
confidence: 99%
“…Relative to normal-weight participants, obese populations exhibit lower gray matter volume, cortical thickness and glucose metabolism in the prefrontal cortex (Pannacciulli et al, 2006;Willeumier et al, 2011;Marqués-Iturria et al, 2014). In striatal structures, individuals with obesity seem to exhibit lower dopamine D2/D3 receptor availability (Wang et al, 2001;De Weijer et al, 2011; but see Eisenstein et al, 2013) and increased gray matter volume . Additionally, functional neuroimaging studies have observed differences between participants with obesity and normal-weight controls during reward processing.…”
Section: Introductionmentioning
confidence: 99%